An Assessment of the International Recruitment of Filipino Nurses to Germany : A Mixed Methods Study - Mary Anne Deveza-Grau (2024)
The recruitment of Filipino nurses for German healthcare institutions started in 2013 with the Triple Win Program. The government-to-government recruitment was supplemented by a Memorandum of Understanding in 2022 to include private recruitment agencies. Methodology: This study uses a mixed methods approach to assess the recruitment of Filipino nurses for Germany by (1) examining data on the deployment of nurses and recognition statistics; and (2) using an online survey, key informant interviews, and review of documents and audiovisual materials to examine the program from the perspectives of Filipino nurses, the Philippines as a source country, and Germany as a destination country. Results: Data from the Department of Migrant Workers revealed that 5.450 nurses were deployed to Germany from 2013 to 2022, 38.9 % of whom were recruited through the Triple Win Program. The Federal Statistics Office registered 15,711 positive outcomes from Filipino applicants in the same period, comprising 14.8 % of the total positive outcomes. The data from the online survey and interviews of nurses revealed that (1) the pre-departure information on nursing practice and language training was inadequate; and (2) access to integration services such as post-arrival language courses, integration officers and intercultural workshops was better in hospitals than in nursing homes (p < 0.001). Moreover, non-nurse respondents noted a lack of data on recruitment from private recruitment agencies, retention, evaluation of various integration programs implemented by healthcare institutions, and measures to mitigate the negative impact of nurse migration on the Philippines. Conclusion: The Philippines is becoming an important source country for nurses. Despite the bilateral agreements made and recent measures implemented by the German government, stakeholders need better collaboration to (1) enhance data collection for assessing the impact of the recruitment and integration programs; (2) improve pre-departure preparation and manage expectations; (3) augment services needed for recruitment and integration through effective networking and coordination.